Large-Scale Sampling Reveals the Strain-Level Diversity of Burkholderia Symbionts in Riptortus pedestris and R. linearis (Hemiptera: Alydidae) - Xin-Rui Hou; Si-Ying Fu; Yuan Wang; Jia-Yue Zhou; Tian-Yi Qi; Yan-Fei Li; Wen-Jun Bu; Huai-Jun Xue (Microorganisms)
Burkholderia (sensu lato) is a diverse group of β-Proteobacteria that exists worldwide in various environments. The SBE clade of this group was thought to be mutualistic with stinkbugs. Riptortus–Burkholderia was suggested as an ideal model system for studying insect–microbe symbiosis. To explore the strain-level diversity of Burkholderia at the individual and population levels of Riptortus stinkbugs (Hemiptera: Alydidae), and to uncover the factors affecting the Burkholderia community, large-scale sampling of two Riptortus species and deep sequencing data (16S amplicon) were used in the present study. Our results showed that: (1) the proportions of facultative symbiotic bacteria Burkholderia were very high, with an average proportion of 87.1% in the samples; (2) only six out of 1373 Burkholderia amplicon sequence variants (ASVs) did not belong to the SBE clade, accounting for only 0.03% of Burkholderia; (3) a relatively small number of Burkholderia ASVs had a large number of sequences, with 22, 54, and 107 ASVs accounting for more than 1.0%, 0.1%, and 0.01% of the total Burkholderia sequences, respectively; (4) multiple Burkholderia ASVs were present in most Riptortus individuals, but there was one dominant or two codominant ASVs, and codominance was more likely to occur when the genetic distance between the two codominant ASVs was small; and (5) the beta diversity of Burkholderia was significantly different between the two host species (PerMANOVA: both Jaccard and Bray–Curtis, p < 0.001) and among localities (PerMANOVA: both Jaccard and Bray–Curtis, p < 0.001). Two-way PerMANOVA also indicated that both the host (Bray–Curtis, p = 0.020; Jaccard, p = 0.001) and geographical location (Bray–Curtis, p = 0.041; Jaccard, p = 0.045) influence Burkholderia communities; furthermore, Mantel tests showed that the Burkholderia communities were significantly correlated with the geographical distance of sample locations (R = 0.056, p = 0.001). Together, our findings demonstrate the fine-scale diversity of Burkholderia symbionts and suggest a region- and host-dependent pattern of Burkholderia in Riptortus stinkbugs.